Mole Robot (MolBot): Development of Pipe Damage Detector Robot. - Vandon Borela; Mark Rodney Dela Peña; Jedd Benedick Salvador; John Nicholas Evangelista; Marlon Hernandez (Journal La Multiapp, 2020)
To get an improved image or to obtain any useful information from it, image processing is a method of implementing any operations on an image. In the method of classifying and detection of images, this process mainly contributes to the innovation of technology. The implementation of image processing in robots had been used in earlier but with different uses. Using FPV Camera 720p OIN in the projects lets it transmits live video streaming to any device attached to it. This paper shows the robustness of image processing as it detects defects on pipes. Covering the inner external part of the pipe, the robot can pass through inside the pipe. With the accuracy of 67%, the project will be tested in different pipes and drainages for the application.